Metabolic syndrome, consumption of ultra-processed foods and sweetened beverages in adolescents - Salustriano, Ingrid Kelly (2024)
Metabolic syndrome is characterized by the concomitant presence of changes in blood glucose, dyslipidemia, elevated blood pressure and excessive adiposity, which increase cardiovascular risk. The objective of this study was to analyze the parameters of metabolic syndrome and the association with the consumption of ultra-processed foods and sweetened beverages in overweight adolescents. A cross-sectional study was carried out with 67 overweight adolescents from a pediatric outpatient clinic of a public hospital in the city of São Paulo. The anthropometric assessment consisted of measuring weight, height and waist circumference. Data on glucose, triglycerides, HDL-c, and blood pressure were collected, and metabolic syndrome (MS) was analyzed according to criteria from the Brazilian Association of Nutrology. Food consumption was assessed using the semi-quantitative food frequency questionnaire. The prevalence of metabolic syndrome was 56.7%. The most prevalent parameters were a reduction in HDL-c (71.6%), and an increase in systolic blood pressure (70.1%) and fasting blood glucose (64.2%). Blood glucose was positively associated with the sweetened beverage consumption score and BMI. It is concluded that there is a high prevalence of metabolic syndrome in adolescents, with glycemia being associated with the consumption of sweetened beverages.